2015
DOI: 10.3402/jecme.v4.27432
|View full text |Cite
|
Sign up to set email alerts
|

Identification of clinician challenges in order to drive the development of competency-based education: results from an international needs assessment in multiple sclerosis

Abstract: Objective. To highlight clinical gaps of neurologists and nurses regarding their skills and confidence in engaging and communicating with multiple sclerosis (MS) patients to inform the design of continuing medical education (CME) initiatives. Methods. This international IRB-approved study deployed in six countries (France, Germany, Italy, Spain, UK and USA), utilised a mixed-methods approach (qualitative interviews and an online survey) to explore the self-reported challenges of neurologists and nurses across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Patients whose healthcare providers respond positively and who provide feedback about their needs, views and concerns are more likely to participate in shared decision-making [ 59 ]. However, studies have shown that doctors and nurses who care for patients with MS sometimes do not have the appropriate knowledge and skills to encourage patients to actively participate in the treatment process [ 73 ]. Therefore, medical personnel should be trained in the communicative and psychological competences in communicating with patients.…”
Section: Adherencementioning
confidence: 99%
“…Patients whose healthcare providers respond positively and who provide feedback about their needs, views and concerns are more likely to participate in shared decision-making [ 59 ]. However, studies have shown that doctors and nurses who care for patients with MS sometimes do not have the appropriate knowledge and skills to encourage patients to actively participate in the treatment process [ 73 ]. Therefore, medical personnel should be trained in the communicative and psychological competences in communicating with patients.…”
Section: Adherencementioning
confidence: 99%
“…However, the same participants self-reported significant deficits in their abilities to engage patients and/or caregivers in SDM due to insufficiencies in knowledge, skill, and confidence. These results suggest that continuing medical education and performance improvement initiatives should be implemented and would be welcomed by practitioners caring for patients with MS. 40 However, the additional time and resources required for training may be an impediment to implementation of such programs. 37 Nonclinical factors, including costs and health care barriers, can also affect adherence and SDM.…”
Section: Sdm and Patient-provider Relationshipmentioning
confidence: 99%
“…As previously highlighted by Hayes SM et al (2015), the relationship between pwMS and MS clinicians includes complexities that, if not properly addressed in medical education, may negatively impact patient adherence to treatment (Hayes et al, 2015). The shared decision-making approach has been shown to facilitate adherence to MS treatment by taking patient values and preferences in consideration (Ben-Zacharia et al, 2018;Colligan et al, 2017;Eskyte et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed neurologists and nurses in MS care report sub-optimal levels of knowledge and confidence when screening patients to initiate or switch DMT, assessing safety of new DMTs and monitoring for adverse events (Ng et al, 2015). Further, there is a need for improvement among neurologists and nurses regarding patient communication skills, particularly when sharing treatment decisions and assessing adherence (Hayes et al, 2015).…”
Section: Introductionmentioning
confidence: 99%